Texture modified diet in German nursing homes: availability, best practices and association with nursing home characteristics - Burger, Carina; Kiesswetter, Eva; Alber, Rowena; Pfannes, Ulrike; Arens-Azevedo, Ulrike; Volkert, Dorothee (BMC Geriatrics, 2019)
BACKGROUND: For nursing home (NH) residents with swallowing or chewing problems, appealing texture-modified-diets (TMD) need to be available in order to support adequate nutrition. The aim of this study was to describe the availability of TMD and best practices for TMD in German NHs and to identify related NH characteristics. METHODS: Information on NH characteristics, available texture-modified (TM)-levels (soft, "minced & moist", pureed) and implemented best practices for TMD (derived from menu plan, separately visible components, re-shaped components, considering individual capabilities of the resident) was collected in a survey in German NHs. The number of TM-levels as well as the number of best practices for TMD were tested for their association with 4 structural, 16 operational and 3 resident-related NH characteristics. RESULTS: The response rate was 7.2% (n = 590) and 563 NHs were included. The vast majority of NHs (95.2%) reported offering "minced & moist" texture and 84.2% preparing separately visible meal components. Several operational characteristics were more frequently (p < 0.05) reported from NHs offering three TM-levels (27.7%) or four best practices for TMD (13.0%) compared to NHs offering one TM-level (28.4%) or one best practice for TMD (20.1%): special diets and delivery forms (e.g. fingerfood 71.2% vs 38.8%; 80.8% vs. 44.3%), written recipes (69.9% vs. 53.1%; 68.5% vs. 53.9%), a dietetic counseling service (85.9% vs. 66.3%; 89.0% vs. 65.2%), a quality circle for nutritional care (66.7% vs. 43.8%; 71.2% vs. 50.4%), regular staff training (89.7% vs. 73.1%; 95.9% vs. 74.8%) and process instructions (73.7% vs. 53.1%; 75.3% vs. 47.8%). No associations were found regarding structural and resident-related NH characteristics, except a higher percentage of residents receiving TMD in NHs with three compared to one TM-level (median 16.3% vs. 13.2%, p = 0.037). CONCLUSION: All participating NHs offer some form of TMD, but only a small number offers a selection of TMD and pays adequate attention to its preparation. Operational NH characteristics - which might reflect a general nutritional awareness of the NH - seem to be pivotal for provision of TMD, whereas neither structural nor resident-related characteristics seem to play a role in this regard.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Chewing problems; Nursing home; Nutritional care; Swallowing problems; Texture modified diet